Tumour Lysis Syndrome In A Neonate With Transient Abnormal Myelopoiesis - A. Mohammad Khuzaini; Mohd Baharudin, J.A.; Md Fauzi, A.; Zulkeflee, H.A.; Abdul Halim, H.,; Mazli, S.K.; Osman, N.F.B. (IOS Press, 2024)
Indexed by Scopus